2018
DOI: 10.3390/ijerph15112574
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis Membranes Influence Perfluorochemical Concentrations and Liver Function in Patients on Hemodialysis

Abstract: Introduction: Perfluoro-octanesulfonate (PFOS) and perfluoro-octanoic acid (PFOA) are two toxic perfluorochemicals (PFCs) commonly used as surfactants. PFCs are difficult to be eliminated from the body. We investigated the influence of different dialysis membranes on the concentrations of PFCs in patients under hemodialysis. Method: We enrolled 98 patients. Of these, 58 patients used hydrophobic polysulfone (PS) dialysis membranes, and the other 40 had hydrophilic membranes made by poly-methyl methacrylate (PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…However, in our study, the PBUT levels in patients on HD did not have statistically significant correlations with the method of dialysis or membrane materials. In another study, it was found that dialysis membranes can have impacts on the levels of perfluorochemicals and could be helpful for patients [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, the PBUT levels in patients on HD did not have statistically significant correlations with the method of dialysis or membrane materials. In another study, it was found that dialysis membranes can have impacts on the levels of perfluorochemicals and could be helpful for patients [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is no proven method to accelerate the clearance of potentially toxic PFAS from the body. Although several strategies have been reported in the literature, including regular phlebotomy, intake of dietary fiber, and hemodialysis therapy, low removal efficiency, and specificity, are limitations. One promising strategy reported by Genuis, Ducatman, and others is the use of a resin-binding drug cholestyramine (CSM). ,, CSM is a bile acid sequestrant (BAS) and has a long history of use for lipid control, is generally regarded as safe, and has been shown to be reasonably efficient for PFAS removal over an extended period of time, especially for PFOS. , Results indicated that ingestion of 4 g/day CSM in three doses for 20 weeks decreased the PFAS serum level compared to pretreatment (23.0 ng/g vs 14.4 ng/g, 5.9 vs 4.1 ng/g, and 58.0 vs 46.8 ng/g for PFOS, PFOA, and PFHxS, respectively) . These results are promising and indeed show accelerated clearance of PFAS in humans after treatment.…”
Section: Fluorinated Compounds For Environmental and Public Healthmentioning
confidence: 99%
“…Interestingly, a previous report by the same group demonstrated that the use of a BPA-free membrane (polynephron) decreased BPA concentrations in peripheral blood mononuclear cells in comparison to the use of a polysulfone membrane [ 26 ]. In this regard, it is unknown how these BPA-free filters could affect other endocrine disruptors (such as perfluorochemicals) [ 27 ].…”
Section: Reducing Bisphenol a In Haemodialysis Patientsmentioning
confidence: 99%